Youth who trade sex in the U.S. : intersectionality, agency, and vulnerability - Showden, Carisa Renae; Majic, Samantha (Temple University Press, 2018)
When cases of domestic minor sex trafficking (DMST) by predatory men are reported in the media, it is often presented that a young, innocent girl has been abused by bad men with their demand for sex and profit. This narrative has shaped popular understandings of young people in the commercialized sex trades, sparking new policy responses. However, the authors of Youth Who Trade Sex in the U.S. challenge this dominant narrative as incomplete. Carisa Showden and Samantha Majic investigate young people's engagement in the sex trades through an intersectional lens. The authors examine the dominant policy narrative's history and the political circumstances generating its emergence and current form. With this background, Showden and Majic review and analyze research published since 2000 about young people who trade sex to develop an intersectional "matrix of agency and vulnerability" designed to improve research, policy, and community interventions that center the needs of these young people. Ultimately, they derive an understanding of the complex reality for most young people who sell or trade sex, and are committed to ending such exploitation.